The 50 Greatest Players in New York Yankees History - Cohen, Robert W. (Rowman & Littlefield Publishers, 2012)
The New York Yankees are Major League Baseball’s most renowned and successful franchise. Baseball greats such as Babe Ruth, Mickey Mantle, and Derek Jeter have all worn the famous navy blue and white pinstripes. The Yankees have won twenty-seven World Series, and twenty-nine players who spent at least a year with the team have been inducted into the Baseball Hall of Fame. With so many Hall of Famers to choose from, selecting the best players in the history of the franchise might seem impossible; yet, that is exactly what Robert W. Cohen has done. This book carefully examines the careers of the players who made the greatest impact on the most successful franchise in the history of professional sports. The ranking was determined based on such factors as the extent to which each player added to the Yankees legacy, the degree to which he impacted the fortunes of his team, and the level of dominance he attained while wearing the Yankee uniform. Features of The 50 Greatest Players in New York Yankees History include Each player’s notable achievements Recaps of the player’s most memorable performances Summaries of each player’s best season Quotes from opposing players and former teammates Yankees fans and baseball fans in general will find The 50 Greatest Players in New York Yankees History a fascinating collection of bios, stats, recaps, quotes, and more. And with such iconic figures as Yogi Berra, Lou Gehrig, Joe DiMaggio, Alex Rodriguez, and Andy Pettitte, this book is sure to inspire debate and controversy among true Yankees fans.